Multiple sclerosis: making the invisibles visible - Chaudhary, Bhupendra; Chaudhary, Ansh (International Journal of Research in Medical Sciences, 2020)
Multiple sclerosis (MS), a chronic inflammatory autoimmune disease with its protean manifestations commonly present as motor weakness, diplopia, visual loss, sensory symptoms in limbs or face or even bladder and bowel dysfunction. Underneath the umbrella of these common symptoms many invisible, unpredictable and erratic symptoms persists which complicates both the clinical presentation and the treatment. As majority of these symptoms are subjective so their true assessment on objective ground is difficult. It is important to consider that patients with MS and their care-takers should have reasonable knowledge about these symptoms because if these symptoms go unidentified or untreated then they may lead to a difficult diagnostic dilemma hence complicates further management. The frequency and severity of these unusual symptoms at times raise a suspicion of other neurological diseases. The occurrence of any of these symptoms at times may be a sign of active disease.